2015
DOI: 10.1242/jeb.129221
|View full text |Cite
|
Sign up to set email alerts
|

Infection with schistosome parasites in snails leads to increased predation by prawns: implications for human schistosomiasis control

Abstract: Schistosomiasis -a parasitic disease that affects over 200 million people across the globe -is primarily transmitted between human definitive hosts and snail intermediate hosts. To reduce schistosomiasis transmission, some have advocated disrupting the schistosome life cycle through biological control of snails, achieved by boosting the abundance of snails' natural predators. But little is known about the effect of parasitic infection on predator-prey interactions, especially in the case of schistosomiasis. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 25 publications
3
44
1
Order By: Relevance
“…Snail demographic data consisted of relative abundance counts between May through July 2014 and October 2015. A time-based snail sampling technique was used analogously to the ones previously used in similar malacological studies ( 6,7,30). Along with snail sampling, a network of wireless micrometeorological stations was installed in each village, allowing for the continuous monitoring of microclimatic and hydrological parameters, including air temperature, water level, conductivity and temperature, and precipitation (36).…”
Section: Methodsmentioning
confidence: 99%
“…Snail demographic data consisted of relative abundance counts between May through July 2014 and October 2015. A time-based snail sampling technique was used analogously to the ones previously used in similar malacological studies ( 6,7,30). Along with snail sampling, a network of wireless micrometeorological stations was installed in each village, allowing for the continuous monitoring of microclimatic and hydrological parameters, including air temperature, water level, conductivity and temperature, and precipitation (36).…”
Section: Methodsmentioning
confidence: 99%
“…Future work may consider the dispersal of infected snails as compared to uninfected snails, as studies have shown that parasitized snails move less than non-parasitized snails [67, 68]. Analyses that consider snail dispersal from upstream to downstream locations within irrigation channels would also be of interest considering the significant association found in this study between irrigation channels and snail retentivity and attractivity.…”
Section: Discussionmentioning
confidence: 97%
“…glabrata and Bu. truncatus exhibit less frequent and slower movement and lower refuge use (above water or under substrate) than uninfected snails in response to predation cues in laboratory trials 27 . The effects and interactions of refuge availability, resource availability (especially as modified by agrochemical contamination), and multiple types of predators on schistosome-infected snail densities clearly deserves further examination.…”
Section: Methodsmentioning
confidence: 92%
“…Although submerged macrophytes might provide snails with a potential refuge from predators 52 , there was no evidence from the mesocosm experiment that the density of H. verticillata affected snail consumption rates by crayfish. However, the effects of refugia on snail population dynamics in natural environments are complex because refuge-seeking behaviors, and growth and reproduction rates of snails can be modified by the types and densities of predators, snail densities, resource availability, and snail infection status 27,53–56 . While a greater availability of refugia in the mesocosm experiments would likely have resulted in higher overall snail densities, the net effects of refugia on infected snail densities are more difficult to predict because prawns (and perhaps crayfish) show a preference for consuming schistosome-infected Bi.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation